Functional outcome of long proximal femoral nail versus short proximal femoral nail in peritrochanteric fractures - Gupta, Sanjeev; Gupta, Pallav; Raina, Gagandeep Singh; Kumar, Manoj; Singh, Gagandeep (International Journal of Research in Medical Sciences, 2021)
Background: Proximal femoral nail (PFN) is an intramedullary implant which has been commonly used in the fixation of intertrochanteric fractures. However, controversy comes about the effect of nail length on fracture union and other complications. A comparative evaluation of surgical treatment and functional outcome of patients with peritrochanteric fractures treated with short versus long PFN. Methods: Total of 100 patients have been included in study out of which 57 belonged to group 1 and were operated with short PFN and rest 43 were group 2 operated with long PFN. Patients were followed up for 6 months and were compared on various parameters. Results: There is no significant difference noted in the two group. However, the surgical duration and blood loss for short PFN was significantly less as compared to long PFN. Conclusions: Short PFN is better implant for peritrochantric fractures both stable and unstable with quicker surgical time and lesser blood loss.